Competition for Partners: Strategic Games in Wholesale International Roaming - Javier Domínguez Lacasa (International Telecommunications Society (ITS), 2011)
High international roaming prices have puzzled and occupied analysts and regulators for quite a time. While on the retail side the problem seems to be well understood, and the high margins can be justified using Ramsey pricing logic, on the wholesale side the picture is not so clear. Recent contributions find reasons for regulation based on the existence of random traffic and on the bilateral nature of the wholesale deals, which raise the equilibrium prices even when operators can choose a preferred network. This paper intends to investigate whether or not those concerns are justified. This is done by modelling the bilateral roaming negotiations and extending the current models, assuming that home operators (the ones with a retail contract with the customer in its country of residence) can decide not only their preferred network in each visited country, but also the distribution of their outbound traffic among the visited operators. We find that when traffic steering is perfect the wholesale market is competitive, and that the lower prices are passed on to end users through competition for retail customers. The bilateral nature of international roaming wholesale deals is actually an additional source of competition on the retail market for mobile services because the roaming out traffic (the traffic of an operator's retail customers abroad) and the roaming in traffic (the traffic of foreign customers that an operator is able to attract) are directly linked.
Keywords: 330